Ortotopic liver Transplantation. Technical Aspects - Pressa, Carlos; Cresseri, Aída; Parodi, José; Esperón, Alejandro; Burghi, Gustavo; Suaya, Hadel (Cirugía del Uruguay, 1983)
Experimental work about technical aspects of ortotopic liver transplantation Hepatectomy technic in donor and receptor is accurated with simultanea! surgical procedures, with double team.